Asymmetric Coupled Dual‐Atom Sites for Selective Photoreduction of Carbon Dioxide to Acetic Acid. (9th August 2022) - Jia, Guangri; Sun, Mingzi; Wang, Ying; Shi, Yanbiao; Zhang, Lizhi; Cui, Xiaoqiang; Huang, Bolong; Yu, Jimmy C.
Abstract: Photocatalytic reduction of CO2 to value‐added liquid fuels is a promising approach to alleviate the global energy and environmental problems. However, highly selective production of C2+ products from CO2 reduction reaction (CO2 RR) is very difficult because of the sluggish CC coupling reaction. An asymmetric coupled heteronuclear photocatalyst is designed to overcome this limitation. The new catalyst contains single atoms of nickel and cobalt loaded on titanium dioxide. It exhibits an impressive 71% selectivity for acetic acid. The experimental data and theoretical calculations reveal that the Ni and Co single atom sites not only significantly lower the energy barrier of electron transfer in photocatalysis but also efficiently promote the CC coupling toward CH3 COOH. The high activity of such a heteronuclear catalyst system will shed light on the future development of effective materials for CO2 RR. Abstract : By introducing asymmetric coupled dual‐atom Ni and Co sites on TiO2, the selectivity for photocatalytic conversion of carbon dioxide to acetic acid is greatly enhanced. This shows the effect of local electron density and low potential barrier on the multi‐electron transfer and multi‐pathway interaction of carbon–carbon dimerization coupling.